Aktualisasi Model Flipped Classroom Berbantuan Media Audio Visual untuk Meningkatkan Hasil Belajar - Agetania, Ni Luh Putu; Marlinda, Ni Luh Putu Mery; Krisna, Evi Dwi (JOEAI (Journal of Education and Instruction), 2023)
This study aimed to enhance the science learning outcomes of Grade 5 students at SD Negeri 5 Padangsambian by implementing the Flipped Classroom Model. This study is an example of Classroom Action Research (CAR). This study's data were collected by administering a multiple-choice scientific learning achievement examination. In analyzing the obtained data, descriptive analysis was utilized. This investigation generated pre-cycle data, cycle I data, cycle II data, and cycle III data. From the data collected prior to the cycle, it was determined that the average class value was 60.42 and the learning completion rate was only 47%. Given that the KKM for science subjects at this institution is 70, this data falls far below expectations. In cycle one, there was an increase, with the class average reaching 72.11 and the mastery learning rate reaching 76%. In cycle two, the class average for learning has reached 79.47, and the completion rate has reached 82%. In cycle three, an average of 85.53 was attained with a 95% completion rate. In conclusion, the application of the Audio Visual-assisted Flipped Classroom Model can enhance science learning outcomes for students in the first semester VA class at SD Negeri 5 Padangsambian during the Flipped Classroom model's school year. Flipped Classroom, Audio-Visual, Learning Outcomes